2022
DOI: 10.1080/24725838.2022.2059594
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Field Testing of Passive Exoskeletons in Several Manufacturing Environments: Perceived Usability and User Acceptance

Abstract: Exploratory field testing of passive exoskeletons in several manufacturing environments: perceived usability and user acceptance OCCUPATIONAL APPLICATIONSResults of the current exploratory study suggest that use of an exoskeleton (EXO) has the potential to be accepted by workers as an intervention in diverse manufacturing environments. Also evident were that the major factors contributing to EXO-use-intention are perceived comfort, task-technology fit, perceived safety, and perceived usefulness. A user's perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Summary statistics were calculated for the results of the Paexo and EVO qualitative questionnaires that were given to participants after testing with the respective EXOs. Questions were based on previous exoskeleton research (Schwerha et al, 2022). The questionnaires measured participant perceptions of a variety of factors.…”
Section: Resultsmentioning
confidence: 99%
“…Summary statistics were calculated for the results of the Paexo and EVO qualitative questionnaires that were given to participants after testing with the respective EXOs. Questions were based on previous exoskeleton research (Schwerha et al, 2022). The questionnaires measured participant perceptions of a variety of factors.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming constant working speed (which we consider valid because participants were encouraged to work at a sustainable working speed) throughout an 8-hr shift at this workplace, this results in a decrease of 120 picks. Schwerha et al ( 2022 ) also reported that workers slowed down due to an exoskeleton and could no longer meet their productivity goals. Contrary to these results, Miura et al ( 2018 ) found that workers’ performance increased significantly when wearing an active lumbar support exoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…While passive devices are less versatile by design, active ones can rely on sensors and algorithms to adapt the assistive output to the demands of the task [13][14][15]. Currently, occupational back support exoskeletons are entering a new development stage in which evaluation of their performance is now expected to take place in field studies [16][17][18]. These studies aim to highlight and verify the potential of exoskeletons to perform as promised by reducing overload and being accepted by workers within industrial environments.…”
Section: Introductionmentioning
confidence: 99%